Late-stage amination of peptides on the solid phase - Brinkhofer, Julian; Werner, Marius; Kokollari, Agon; Pan, Shih-Yu; Klein, Christian D.; Pham, Truc Lam; Thomas, Franziska (Chemistry - a European journal, 2025)
Late-stage peptide modification is a powerful tool for rapidly generating a library of peptide mimetics, for example, for drug discovery or catalyst development. While late-stage modifications exist for many types of structural features, methods for introducing amines into peptides via a late-stage approach are rare, despite their enormous potential for the development of peptide therapeutics. Here we present a protocol for introducing amines into peptides by our established on-resin iodination-substitution approach. Our method is compatible with a wide variety of amines, including primary and secondary amines, anilines, and other heteroaromatic N-nucleophiles mostly giving good to excellent yields. We introduce amines that are pharmacologically relevant as well as those that can impart catalytic or metal-binding properties into the peptide of interest. As a proof-of-concept study, we introduce the metal ligand tris(2-aminoethyl)amine (tren) into a tryptophan zipper scaffold using our late-stage amination approach to explore metal-induced stapling. Indeed, metal complexation via the tren ligand resulted in a thermal stabilization of more than 30 K in one of our tryptophan zipper designs.
Gesehen am 09.09.2025